Implementation of Community Service Programmes in Shaping the Social Character of Islamic Boarding School Students - Sintasari, Beny; Maghfiroh, Amalia; Tohir, Mastor Bin Mohd (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyse the implementation of community service programmes in shaping the social character of students at the Abdul Hadi Diwek Islamic Boarding School in Jombang. The background of this study is based on the challenges of globalisation, which has the potential to weaken the values of empathy, responsibility, and social awareness, even in Islamic boarding schools. Therefore, community service programmes are seen as a strategic medium for strengthening character education based on real experiences. This study uses a qualitative approach with a case study design. The research subjects consist of Islamic boarding school caregivers, the head of Madrasah Diniyah, and santri who are involved in teaching and cooperatives. Data were collected through participatory observation, in-depth interviews, and documentation, then analysed using interactive reduction, presentation, and conclusion-drawing techniques. Data validity was maintained through triangulation of sources and methods. The results showed that the implementation of the community service programme took place in three stages, namely planning, implementation, and evaluation. The planning stage was carried out systematically by setting objectives and dividing the areas of service according to the students' abilities. The implementation was structured with assignments at Madrasah Diniyah and cooperatives, which fostered discipline and responsibility. Evaluation was carried out periodically through deliberations and guidance from supervisors, so that students could improve their shortcomings while strengthening their strengths.